Edible insects are the future?. Issue 3 (24th February 2016) - van Huis, Arnold
Abstract : The global increase in demand for meat and the limited land area available prompt the search for alternative protein sources. Also the sustainability of meat production has been questioned. Edible insects as an alternative protein source for human food and animal feed are interesting in terms of low greenhouse gas emissions, high feed conversion efficiency, low land use, and their ability to transform low value organic side streams into high value protein products. More than 2000 insect species are eaten mainly in tropical regions. The role of edible insects in the livelihoods and nutrition of people in tropical countries is discussed, but this food source is threatened. In the Western world, there is an increasing interest in edible insects, and examples are given. Insects as feed, in particular as aquafeed, have a large potential. Edible insects have about the same protein content as conventional meat and more PUFA. They may also have some beneficial health effects. Edible insects need to be processed and turned into palatable dishes. Food safety may be affected by toxicity of insects, contamination with pathogens, spoilage during conservation and allergies. Consumer attitude is a major issue in the Western world and a number of strategies are proposed to encourage insect consumption. We discuss research pathways to make insects a viable sector in food and agriculture: an appropriate disciplinary focus, quantifying its importance, comparing its nutritional value to conventional protein sources, environmental benefits, safeguarding food safety, optimising farming, consumer acceptance and gastronomy.